2017
DOI: 10.1038/nsmb.3439
|View full text |Cite
|
Sign up to set email alerts
|

An antimicrobial peptide that inhibits translation by trapping release factors on the ribosome

Abstract: Many antibiotics stop bacterial growth by inhibiting different steps of protein synthesis. However, no specific inhibitors of translation termination are known. Proline-rich antimicrobial peptides, a component of the antibacterial defense system of multicellular organisms, interfere with bacterial growth by inhibiting translation. Here we show that Api137, a derivative of the insect-produced antimicrobial peptide apidaecin, arrests terminating ribosomes using a unique mechanism of action. Api137 binds to the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
213
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(246 citation statements)
references
References 65 publications
27
213
0
Order By: Relevance
“…70S ribosomes from E. coli MRE600, initiation factors (IF1, IF2, IF3), elongation factors (EF-Tu, EF-G), RF1, fMet-tRNA fMet , BODIPY-Met-tRNA fMet and Phe-tRNA Phe were prepared from E. coli as described (32,(33)(34)(35)(36)(37)(38)(39). Gln-, Ala-and Asn-tRNA mixture, Arg-tRNA Arg , Gly-tRNA Gly , Val-tRNA Val were prepared from E. coli total tRNA by aminoacylation with the respective amino acid and subsequent affinity chromatography of the EF-Tu-GTP-aa-tRNA ternary complexes on Protino Ni-IDA 2000 Packed Columns (Macherey-Nagel) followed by phenolization and ethanol precipitation of aa-tRNA.…”
Section: Trna Preparationmentioning
confidence: 99%
“…70S ribosomes from E. coli MRE600, initiation factors (IF1, IF2, IF3), elongation factors (EF-Tu, EF-G), RF1, fMet-tRNA fMet , BODIPY-Met-tRNA fMet and Phe-tRNA Phe were prepared from E. coli as described (32,(33)(34)(35)(36)(37)(38)(39). Gln-, Ala-and Asn-tRNA mixture, Arg-tRNA Arg , Gly-tRNA Gly , Val-tRNA Val were prepared from E. coli total tRNA by aminoacylation with the respective amino acid and subsequent affinity chromatography of the EF-Tu-GTP-aa-tRNA ternary complexes on Protino Ni-IDA 2000 Packed Columns (Macherey-Nagel) followed by phenolization and ethanol precipitation of aa-tRNA.…”
Section: Trna Preparationmentioning
confidence: 99%
“…To understand whether RF3 can dissociate from the N state when RF1 is bound, we used apidaecin 137 (Api), an antibiotic that enters the polypeptide exit tunnel after peptide release, interacts with RF1 and blocks RF1 dissociation from the PostHC (Florin et al, 2017).…”
Section: Interplay Between Rf1 and Rf3mentioning
confidence: 99%
“…In the P/E conformation, the anticodon stem loop remains in the 30S P site, while the elbow and acceptor arm bind the L1 stalk and E site of the 50S subunit. A recent cryo-EM study (Graf et al, 2018) showed that if RF1 is locked on the post-hydrolysis ribosome by antibacterial peptide apidaecin 137 (Florin et al, 2017), the ribosome can undergo intersubunit rotation in the presence of both RF1 and RF3. By contrast, biochemical experiments showed that locking RF1 on the ribosome by inactivating its catalytic motif (GGQ-> GAQ) prevented RF1 recycling by RF3 from the pre-hydrolysis ribosome (Koutmou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%